Experiences and academic alternatives of the University of Medical Sciences of Cienfuegos during COVID-19 - María Aurelia San Juan Bosch; Rubén Darío García Núñez; Norma Mur Villar; Arelys Falcón Hernández; Alexis Díaz Brito (Medisur, 2020)
Foundation: maintaining health professionals´ training with alternative methods that allow the educational teaching process to continue is a necessity at the present stage of COVID-19. Objective: to expose the experiences, academic rearrangement variants and alternatives developed at the Cienfuegos University of Medical Sciences in times of the Covid-19 pandemic. Methods: this work was developed from a general systemic approach and with the application of theoretical (analytical-synthetic; inductive-deductive) and empirical-level methods such as documentary analysis. Results: developed experiences and alternatives of teaching rearrangement have had the purpose of guiding appropriately to act safely and proactively in complex circumstances and for which there was no history; they constitute a stimulus for incorporating alternative scenarios, using remote technology, digital resources and a reinforcement of medical education social mission. Conclusions: alternatives aimed at reordering the educational teaching process, adapted to current conditions of the public health context in pandemic times, have enabled the training process continuity.